2006
DOI: 10.1093/europace/eul058
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metastasis of malignant melanoma: a rare cause of complete atrioventricular block

Abstract: Malignant melanoma has an aggressive biological behaviour and a high rate of cardiac involvement. As shown from post-mortem studies, metastases of melanoma can involve any organ and cardiac metastases are frequent. This report describes a case of widespread malignant melanoma in a patient with clinical presentation of complete atrioventricular (AV) block. Thorax CT and transthoracic echocardiography revealed a mass involving the conduction system. By VDD permanent pacing (atrial synchronous ventricular pacing)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…However, myocardial metastases can cause sudden death or other significant clinical problems such as syncope, and indeed, such cases have been previously reported. For example, myocardial metastases can provoke atrial and ventricular heart rhythm disturbances and conduction defects, including complete atrioventricular block (5)(6)(7)(8)(9), and may cause myocardial infarction or angina pectoris as a result of invasion or compression of a coronary artery (1,(10)(11)(12). Although there are no established therapeutic strategies, several reports have shown that, in patients whose myocardial metastasis caused complete atrioventricular block, pacemaker implantation or systemic chemotherapy might be effective (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…However, myocardial metastases can cause sudden death or other significant clinical problems such as syncope, and indeed, such cases have been previously reported. For example, myocardial metastases can provoke atrial and ventricular heart rhythm disturbances and conduction defects, including complete atrioventricular block (5)(6)(7)(8)(9), and may cause myocardial infarction or angina pectoris as a result of invasion or compression of a coronary artery (1,(10)(11)(12). Although there are no established therapeutic strategies, several reports have shown that, in patients whose myocardial metastasis caused complete atrioventricular block, pacemaker implantation or systemic chemotherapy might be effective (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant melanoma is the neoplasm most frequently involving the heart [4][5][6][7]. Cardiac metastases of malignant melanomas are diagnosed with increasing frequency, because of the rising incidence and increasing survival of patients with melanoma [8].…”
Section: Image Of the Monthmentioning
confidence: 99%
“…Despite massive involvement they are only rarely detected ante mortem (< 30%), because clinical signs and symptoms are often unclear and nonspecific [4]. By contrast, cardiac involvement is found at autopsy in > 50-65% of patients with metastatic malignant melanoma [5,8].…”
Section: Image Of the Monthmentioning
confidence: 99%
“…8 In cases where invasion of the myocardium is present, supraventricular and ventricular arrhythmias also may be observed. 9,10 Monomorphic ventricular tachycardia is one of the most frequently reported types of cardiac metastasis-related ventricular arrhythmia in both children and adults. [11][12][13][14] In contrast, polymorphic ventricular tachycardia (PMVT) in the setting of cardiac metastasis has been reported only once.…”
Section: Introductionmentioning
confidence: 99%